1994
DOI: 10.1007/bf00157965
|View full text |Cite
|
Sign up to set email alerts
|

The localization of mercury and metallothionein in the cerebellum of rats experimentally exposed to methylmercury

Abstract: Rats were dosed with methylmercuric chloride, either by gastric gavage (5 x 10 mg kg-1 body weight over a 15-day period), or in their drinking water (20 mg methylmercuric chloride l-1 for 14 or 42 days). Localization of mercury within the cerebellum was performed with a silver physical development technique, and metallothionein with dinitrophenyl hapten-sandwich immunohistochemistry. Mercury was detected in structurally undamaged Purkinje neurones and adjacent Bergmann glial cells; no mercury was detected in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Likewise, GABA-evoked currents in cerebellar granule cells in culture also seem to be much more sensitive to block by MeHg than are currents mediated by voltage-gated K ϩ channels or inwardly rectifying K ϩ channels. As noted above, cerebellar granule cells are more sensitive to MeHg-induced cytotoxicity than are Purkinje cells in vivo (Leyshon-Borland et al, 1994) and in vitro (Edwards et al, 2005) and sIPSCs in granule cells are 2ϫ to 3ϫ more sensitive to block by MeHg than are those in Purkinje cells (Yuan and Atchison, 2003). However, in many cases, after sIPSCs in granule cells were blocked completely, washing with MeHg-free solution containing 1 mM D-penicillamine, a MeHg chelator, completely restored the sIPSCs to preMeHg treatment level, whereas recovery was not seen in Purkinje cells (Yuan and Atchison, 2003).…”
Section: Differential Effects Of Mehg On Glutamatergic Andmentioning
confidence: 85%
“…Likewise, GABA-evoked currents in cerebellar granule cells in culture also seem to be much more sensitive to block by MeHg than are currents mediated by voltage-gated K ϩ channels or inwardly rectifying K ϩ channels. As noted above, cerebellar granule cells are more sensitive to MeHg-induced cytotoxicity than are Purkinje cells in vivo (Leyshon-Borland et al, 1994) and in vitro (Edwards et al, 2005) and sIPSCs in granule cells are 2ϫ to 3ϫ more sensitive to block by MeHg than are those in Purkinje cells (Yuan and Atchison, 2003). However, in many cases, after sIPSCs in granule cells were blocked completely, washing with MeHg-free solution containing 1 mM D-penicillamine, a MeHg chelator, completely restored the sIPSCs to preMeHg treatment level, whereas recovery was not seen in Purkinje cells (Yuan and Atchison, 2003).…”
Section: Differential Effects Of Mehg On Glutamatergic Andmentioning
confidence: 85%
“…In addition, Mukai (1972) observed that astroglial cells conveyed the mercury-protein complex into neurons using autoradiographic study after the administration of ethyl mercury-S-cysteine labeled with tritium; thus, it is thought that astrocytes are the first target against organic mercury. Leyshon-Sørland et al (1994) reported that mercury was detected in undamaged Purkinje neurons and adjacent Bergmann glial cells when methyl mercury was administered orally to rats over 14 days, and MT-1 and MT-2 were detected in Bergmann glial cells, Purkinje cells, astrocytes, and glial cells of white matter in the cerebellum. Moreover, the expression of MT-1 protects astrocytes against the cytotoxic effects of methyl mercury (Yao et al 1999(Yao et al , 2000, and Giralt et al (2001) observed that MT-1 mRNA and protein increase in the Purkinje, granular layers, and white matter tracts of the cerebellum of GFAP-IL3 mice.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, wherever a MeHg compound has been identified in biological media, it has been complexed to —SH‐containing ligands. However, MeHg has been reported to weakly bind to MT compared with the inorganic species Hg 2+ or Cd, 83–85 and it remains to be established whether the binding of MeHg to MT is associated with the attenuated effects on RVD and taurine release.…”
Section: Metallothioneins: Regulation Function and Distributionmentioning
confidence: 99%